Enhancing MSME Competitiveness In The Creative Industry Through Human Resources Development In South Tangerang - Aidil Amin Effendy; Denok Sunarsi; Wawan Supriyatna; Imas Masriah; Ahmad Nurhadi (Jurnal Manajemen Industri dan Logistik, 2025)
This study aims to determine the strategy to increase the competitiveness of creative industry MSMEs in the digital era through human resource development in the creative industry, especially the Wood Processing Industry in South Tangerang. Findings reveal that HR development especially in digital skills training such as product design, online marketing, and online store management combined with the integration of technology into production processes, significantly improves efficiency, productivity, and market reach. Social media platforms, particularly WhatsApp, Instagram, and TikTok, are essential tools for marketing and customer engagement. The study contributes to the literature by providing an applied framework for enhancing MSME competitiveness through targeted HR capacity building and digital adaptation strategies. This study concludes that although there have been efforts to take advantage of digital opportunities, there is still room for further development in the use of technology and more effective online marketing strategies.